2009
DOI: 10.2319/081808-435.1
|View full text |Cite
|
Sign up to set email alerts
|

Malposition of Unerupted Mandibular Second Premolar in Children with Palatally Displaced Canines

Abstract: Objective: To test the hypotheses that (1) the distal angulation of unerupted mandibular premolar (MnP2) is significantly greater in children with palatally displaced canines (PDC) than in those in a control sample; and (2) delayed tooth formation is significantly more frequent in children with both malposed MnP2 and PDC than in children with PDC only. Materials and Methods: We examined retrospectively panoramic radiographs from 43 patients with PDC who had no previous orthodontics. A control sample consisted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 12 publications
0
9
0
3
Order By: Relevance
“…PDC and MnP2 malposition have also been proven to be significantly related, suggesting a common genetic etiology, despite taking place on opposite jaws. 15,16 Agenesis of MnP2 and distally displaced premolars have been previously associated in other studies 4,20 ( Figure 3). The study that inspired us, by Shalish et al, 20 showed an almost 10u mean distal angle increase in the agenesic sample compared with an age-and sex-matched control group.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…PDC and MnP2 malposition have also been proven to be significantly related, suggesting a common genetic etiology, despite taking place on opposite jaws. 15,16 Agenesis of MnP2 and distally displaced premolars have been previously associated in other studies 4,20 ( Figure 3). The study that inspired us, by Shalish et al, 20 showed an almost 10u mean distal angle increase in the agenesic sample compared with an age-and sex-matched control group.…”
Section: Discussionmentioning
confidence: 91%
“…S. Peck,17 ,18 S. Peck and colleagues, 7,8,11,19 Baccetti,10,12 Baccetti and colleagues, 16 Garib and colleagues, 4 Shalish and colleagues, 5,15,20 and L. Peck and colleagues 13 are prominent among those who have contributed recently to an increased awareness of fundamental relationships among dental abnormalities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The choice of this threshold was based on results of previous studies introducing this positional anomaly. [27][28][29][30][31] The standardized method for measuring MnP2-DA described by Shalish et al 27 was employed.…”
Section: Dental Anomalies Associated With Infraocclusionmentioning
confidence: 99%
“…Shalish et al 2,17,18 noted that among populations of European ethnicities, significant distal inclination of the unerupted MnP2 is found not only in cases of unilateral MnP2 agenesis, but also among individuals having cleft lip/palate and palatally displaced canines.…”
Section: Discussionmentioning
confidence: 99%